2017
DOI: 10.5152/iao.2017.4203
|View full text |Cite
|
Sign up to set email alerts
|

The Adenoid Microbiome in Recurrent Acute Otitis Media and Obstructive Sleep Apnea

Abstract: OBJECTIVE:To compare the microbial flora of adenoids from patients with recurrent acute otitis media (AOM) and patients with obstructive sleep apnea (OSA). MATERIALS and METHODS:This study was prospective and controlled. Adenoids were obtained from children undergoing adenoidectomy for recurrent AOM (n=7) or OSA (n=13). Specimens were processed for total deoxyribonucleic acid (DNA) isolation. 16s DNA 454-pyrosequencing was performed on AOM (n=5) and OSA (n=5) specimens. All specimens were analyzed by real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…A prior study children with recurrent AOM found Alloiococcus , Staphylococcus sp. and Turicella were most abundant in the ME (Lappan et al, 2018), whereas adenoids microbiome was dominated by H. influenzae , M. catarrhalis , S. pneumoniae , P. aeruginosa , and S. aureus (Dirain et al, 2017). On the other hand, in chronic otitis media, Krueger et al reported that the Haemophilus and Moraxella were the most abundant microbiota in the ME of children (Krueger et al, 2017), whereas Liu et al reported that Pseudomonadaceae dominated in the ME, Streptococcaceae in the tonsil, and Pseudomonadaceae, Streptococcaceae, Fusobacteriaceae, and Pasteurellaceae dominated in the adenoid (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A prior study children with recurrent AOM found Alloiococcus , Staphylococcus sp. and Turicella were most abundant in the ME (Lappan et al, 2018), whereas adenoids microbiome was dominated by H. influenzae , M. catarrhalis , S. pneumoniae , P. aeruginosa , and S. aureus (Dirain et al, 2017). On the other hand, in chronic otitis media, Krueger et al reported that the Haemophilus and Moraxella were the most abundant microbiota in the ME of children (Krueger et al, 2017), whereas Liu et al reported that Pseudomonadaceae dominated in the ME, Streptococcaceae in the tonsil, and Pseudomonadaceae, Streptococcaceae, Fusobacteriaceae, and Pasteurellaceae dominated in the adenoid (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, some pathogens have adapted to NETs, particularly H. influenzae, which can initiate NETs and tightly associate with these structures, avoiding phagocytic escape, thus resulting in chronic infection [37]. In fact, this pathogen is a leading cause of ROAM, as already reported by some studies [38,39].…”
Section: Discussionmentioning
confidence: 81%
“…Higher abundances of the genera Haemophilus, Fusobacterium, and Porphyromonas were found in the adenoids and tonsils of our pediatric OSA group. Haemophilus is the main pathogenic bio lm bacteria constituting the adenoid reservoir (23,24). Fusobacteria were detected at a tonsillar site in pediatric OSA patients (25) and associated with the AHI (20).…”
Section: Discussionmentioning
confidence: 99%